Exploring leadership styles of leaders in relation to the homestay programme perfomance in Langkawi - Sharon Esther, Donny Sita (2024)
A homestay programme is one of the initiatives taken by the government through the Ministry of Tourism, Arts and Culture (MOTAC) to improve the lifestyle and the economic progress of the rural population. The programme managed by local leaders serves as a platform for villagers to generate side income by selling local products, besides introducing the village and its surrounding natural beauty to tourists. However, the existing homestay programme operators face several obstacles in generating lucrative income due to programme inactivity, thus resulting in their withdrawal from the programme. This has become a challenge for programme leaders in ensuring the success of the programme and in gaining continuous support from programme hosts. As such, this study identified the leadership styles of homestay programme leaders in managing and influencing hosts towards a successful implementation of homestay programme in Langkawi. This qualitative study deployed the purposive sampling techniques to capture feedback from a host of respondents involved in three active homestay programmes in Langkawi, namely Desa Wang Tok Rendong Homestay. Kampung Padang Lalang Homestay, and Pulau Tuba Homestay. In total, thirteen respondents (ten hosts and three leaders) were interviewed based on a semi-structured format to gather primary data. The secondary data, which comprised of relevant supporting documents, were analysed. The results revealed that cooperation and networking, use of resources, tourist arrivals and total programme income are some success indicators of the homestay programmes in Langkawi. A number of challenges faced by the participants when implementing the programme were identified. The leadership styles practised by the leaders of the three homestay programmes were linked to their vision, decision-making process, and leader-host relationship. With the cooperation received from MOTAC, the Institute for Rural Advancement (INFRA) could organise more leadership courses for homestay hosts. In addition, technology courses are available to encourage the participants to use technology as a medium to digitally promote the homestay programme. These initiatives offer vast opportunities and platforms for various parties, such as MOTAC, INFRA, homestay programme leaders, and programme hosts, to work together in ensuring the success of homestay programme, particularly in Langkawi and generally in Malaysia